2009
DOI: 10.1002/ajp.20679
|View full text |Cite
|
Sign up to set email alerts
|

Fetal, infant, adolescent and adult phenotypes of polycystic ovary syndrome in prenatally androgenized female rhesus monkeys

Abstract: Old World monkeys provide naturally-occurring and experimentally-induced phenotypes closely resembling the highly prevalent polycystic ovary syndrome (PCOS) in women. In particular, experimentally-induced fetal androgen excess in female rhesus monkeys produces a comprehensive adult PCOS-like phenotype that includes both reproductive and metabolic dysfunction found in PCOS women. Such a reliable experimental approach enables the use of the prenatally androgenized (PA) female rhesus monkey model to (1) examine f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
2
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(129 citation statements)
references
References 86 publications
6
118
2
3
Order By: Relevance
“…Animal models have shown that prenatal androgen treatment induce accelerations of LH pulsatile release in primates (Abbott et al 2009), sheep (Forsdike et al 2007, Steckler et al 2009), and rodents (Foecking et al 2005), in accordance with the present results. Our observations confirm the concept that an early disturbance due to intrauterine androgen excess reprograms nervous tissue development of the fetus and irreversibly alters neuroendocrine function in female offspring.…”
Section: Discussionsupporting
confidence: 92%
“…Animal models have shown that prenatal androgen treatment induce accelerations of LH pulsatile release in primates (Abbott et al 2009), sheep (Forsdike et al 2007, Steckler et al 2009), and rodents (Foecking et al 2005), in accordance with the present results. Our observations confirm the concept that an early disturbance due to intrauterine androgen excess reprograms nervous tissue development of the fetus and irreversibly alters neuroendocrine function in female offspring.…”
Section: Discussionsupporting
confidence: 92%
“…PNA female nonhuman primates show reproductive and metabolic disturbances such as polycystic ovaries, hyperandrogenism, oligomenorrhea, oligo-or anovulation, and LH hypersecretion, which are consistent with the human PCOS phenotype (Abbott et al 2008a,b). Furthermore, intrauterine androgen exposure in these monkeys leads to the development of insulin resistance associated with visceral adiposity, impaired glucose metabolism, and dyslipidemia (Abbott et al 2009). These observations substantiate the hypothesis that an early perturbation due to in utero androgen excess resets the reproductive and metabolic trajectory of the growing fetus and programs target tissue differentiation and development, supporting a potential role of epigenetics and fetal programming in the pathogenesis of PCOS (Franks 2012).…”
mentioning
confidence: 99%
“…The origins of PCOS have been proposed to extend back to foetal life. Exposure to androgens during gestation led to the development of PCOS by female rhesus monkeys (Abbott et al 2009), sheep (Veiga-Lopez et al 2008 and rats (Demissie et al 2008), with characteristics similar to those observed in humans. Interestingly, treatment of adult monkeys with androgens in various forms and regimens failed to induce PCOS (Billiar et al 1985).…”
Section: Foxl2: a Key Regulator Of Ovarian Developmentmentioning
confidence: 67%
“…The authors postulate that expression of fibrillin 3 at this time may predispose the foetus to develop PCOS in later life. To prevent the propagation of PCOS or metabolic-related disorders from mothers to daughters, interventions to prevent increased weight gain/adiposity during adolescence have been proposed (Abbott et al 2009). …”
Section: Foxl2: a Key Regulator Of Ovarian Developmentmentioning
confidence: 99%